Tidal polarizability effects in neutron star mergers. (April 2015) - Bernuzzi, S; Nagar, A; Balmelli, S; Dietrich, T; Ujevic, M
Abstract: Using the analytical effective-one-body model and nonlinear 3+1 numerical relativity simulations, we investigate binary neutron star mergers. It is found that, for nonspinning binaries, both the mass-rescaled gravitational wave frequency at merger and the specific binding energy at merger almost uniquely depend on the tidal coupling constants κ T 2, which are functions of the stars' Love numbers, compactnesses and mass ratio. These relations are quasiuniversal in the sense that there is an additional dependence on the spins, which is linear for realistic spins values χ ≲ 0.1. In the effective-one-body model, the quasiuniversality is a direct consequence of the conservative dynamics of tidally interacting bodies. In the context of gravitational wave astronomy, our findings may be used to constrain the neutron stars' equation of state using waveforms that accurately model the merger.